Immune and vascular contributions to organogenesis of the testis and ovary. (12th April 2021) - Gu, Xiaowei; Li, Shu‐Yun; DeFalco, Tony
Abstract : Gonad development is a highly regulated process that coordinates cell specification and morphogenesis to produce sex‐specific organ structures that are required for fertility, such as testicular seminiferous tubules and ovarian follicles. While sex determination occurs within specialized gonadal supporting cells, sexual differentiation is evident throughout the entire organ, including within the interstitial compartment, which contains immune cells and vasculature. While immune and vascular cells have been traditionally appreciated for their supporting roles during tissue growth and homeostasis, an increasing body of evidence supports the idea that these cell types are critical drivers of sexually dimorphic morphogenesis of the gonad. Myeloid immune cells, such as macrophages, are essential for multiple aspects of gonadogenesis and fertility, including for forming and maintaining gonadal vasculature in both sexes at varying stages of life. While vasculature is long known for supporting organ growth and serving as an export mechanism for gonadal sex steroids in utero, it is also an important component of fetal testicular morphogenesis and differentiation; additionally, it is vital for ovarian corpus luteal function and maintenance of pregnancy. These findings point toward a new paradigm in which immune cells and blood vessels are integral components of sexual differentiation and organogenesis. In this review, we discuss the state of the field regarding the diverse roles of immune and vascular cells during organogenesis of the testis and ovary and highlight outstanding questions in the field that could stimulate new research into these previously underappreciated constituents of the gonad. Abstract : Vasculature and immune cells are traditionally known for their supportive roles in tissue growth and immunity. However, increasing evidence suggests that these cell types are critical, active drivers of organogenesis, in particular within the reproductive system. Here we review the diverse roles of vasculature and immune cells in morphogenesis, differentiation, and function of the testis and ovary. These findings could provide new insights into our understanding of development and disease.